2019
DOI: 10.1055/s-0039-1694007
|View full text |Cite
|
Sign up to set email alerts
|

Low Bioactive Vitamin D Is Associated with Pregnancy-Induced Hypertension in a Cohort of Pregnant HIV-Infected Women Sampled Over a 23-Year Period

Abstract: Objective To examine the association of vitamin D insufficiency and risk of pregnancy-induced hypertension (PIH) among human immunodeficiency virus (HIV)-infected pregnant women. Study Design This is a retrospective cohort study evaluating the impact of low maternal vitamin D levels on PIH and perinatal outcomes among HIV-infected pregnant women receiving care at an urban HIV center from 1991 to 2014. Results A total of 366 pregnant women were included, of which 11% developed PIH. Lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
(64 reference statements)
1
8
0
Order By: Relevance
“…Although correlation does not imply causation, our results, together with the well-known ability of placental calcitriol to reach the maternal circulation [ 10 , 11 , 12 ] and act as a negative endocrine regulator of RAS [ 48 ], strongly support a role of placental calcitriol in the control of maternal blood pressure. In agreement with our observations, low maternal calcitriol serum levels in a cohort of infected women have been associated with pregnancy-induced hypertension and group B Streptococcus colonization [ 49 ]. Moreover, calcitriol is known to exert a potent vasodilator effect due to the presence of the vitamin D receptor in blood vessels, playing an essential role in endothelial cell function and blood pressure control [ 50 , 51 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although correlation does not imply causation, our results, together with the well-known ability of placental calcitriol to reach the maternal circulation [ 10 , 11 , 12 ] and act as a negative endocrine regulator of RAS [ 48 ], strongly support a role of placental calcitriol in the control of maternal blood pressure. In agreement with our observations, low maternal calcitriol serum levels in a cohort of infected women have been associated with pregnancy-induced hypertension and group B Streptococcus colonization [ 49 ]. Moreover, calcitriol is known to exert a potent vasodilator effect due to the presence of the vitamin D receptor in blood vessels, playing an essential role in endothelial cell function and blood pressure control [ 50 , 51 ].…”
Section: Discussionsupporting
confidence: 92%
“…Various clinical and epidemiological studies have suggested a correlation between VD-deficiency and high blood pressure in different clinical and physiological settings [ 13 , 14 , 15 , 18 , 19 , 20 , 48 , 49 ]; however, this is the first study showing an inverse correlation between umbilical venous serum calcitriol and both SBP and DBP of pregnant subjects with UTI. Interestingly, significantly lower SBP and DBP have been reported among children and adolescents with higher cord-calcidiol levels at birth [ 21 , 57 ].…”
Section: Discussionmentioning
confidence: 86%
“…There is growing evidence suggesting the importance of vitamin D in placental-related functions including placental development and implantation, calcium transport, immunomodulatory functions, as well as an association between low calcitriol levels and pregnancy induced hypertension. [15,[30][31][32][33] During pregnancy, non-classical, extra-renal production of 1,25(OH)D 2 occurs in the placenta. In fact, healthy pregnancy is associated with a doubling or tripling of pre-pregnancy 1,25(OH)D 2 levels while 25(OH)D levels typically remain unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that this effect of GBS colonization on cathelicidin mRNA levels was largely mediated by cubulin and CYP27B1 mRNA expression, further supporting the idea that vitamin D and its metabolites support antimicrobial peptide production. 66 In another study, vitamin D levels in cord blood at birth were used to investigate the link between vaginal carriage of GBS and maternal vitamin D levels. GBS vaginal carriage was significantly greater in women whose newborns showed deficient (<10 mg/mL) or insufficient (10− 30 mg/mL) vitamin D levels at birth compared to women whose newborns showed sufficient (>30 mg/mL) vitamin D levels at birth.…”
Section: ■ Vitamin D Deficiency and Susceptibility To Streptococcal I...mentioning
confidence: 75%
“…Vitamin D deficiency is associated with increased risk of infection and supplementation alters host–pathogen interactions. Micronutrient deficiencies, such as vitamin D inadequacy, has been associated with increased risk of infection, including those caused by Streptococcus . , Specifically, vitamin D deficiency has been correlated with increased risk of community acquired streptococcal pneumonia and tonsillopharyngitis. , Neutrophils upregulate CYP27B1 in the presence of IFN-y thus resulting in the upregulation of alpha-defensins (HNP1–3) that mediates the killing of pneumococci . A retrospective study of 54 patients with recurrent tonsillopharyngitis caused by GAS demonstrated that serum levels of vitamin D (25­(OH)­D) less than 20 ng/mL were associated with the disease .…”
Section: Vitamin D Deficiency and Susceptibility To Streptococcal Inf...mentioning
confidence: 99%